Determination of Strong Factor in Bird Strike Analysis using Taguchi`s method for Aircraft Manufacturing guide. Issue 1 (January 2021) - Mathaiyan, Vijayakumar; Vijayanandh, R.; Jung, Dong Won
Abstract: Bird strike analysis is of great importance because of the loss it can create. Since there are many factors which influences the level of damage, the computational cost for determining the strong factor is high. Usage of the optimization techniques will give the significant reduction of computational cost. Taguchi method is used to find out the strong factors for a detailed study of bird strike effects on the Aircrafts. This can help the engineers to manufacture the structure free from or have relatively less damage because of the bird strike.